Pengaruh Range Of Motion Aktif terhadap Pemulihan Kekuatan Otot dan Sendi Pasien Post Op Fraktur Ekstremitas di Wilayah Kerja Puskemas Muara Kumpeh - Rino M; Jufri Al Fajri (Universitas Baiturrahim, 2021)
Fracture is a break in bone continuity and is determined according to its type and extent (Anita, 2015). Fractures caused by injuries include falls, traffic accidents and trauma to sharp or blunt objects. The trend of injury prevalence shows an increase from 7.5% in 2017 to 8.2% in 2018 (Kemenkes RI, 2018). This research is a quantitative research with pre-experimental research methods with one group pretest and posttest research design. This study was conducted to determine the effect of restoring muscle and joint strength in post-op patients with limb fracture in the working area of Muara Kumpeh puskemas. The research time is planned to be carried out on July 15, 2020 in the working area of the Muara Kumpeh Health Center. The population in this study was Post op fracture with a number of 84 people. The sample in this study was 15 people using purposive sampling method. Data collection was carried out by observing the respondents MMT (Manual Muscle Testing). research using the T-Test. The results showed that the average value of muscle and joint strength recovery in post-op limb fracture patients before therapy was 30.20 Mean while the average value of muscle and joint strength recovery in post-op limb fracture patients after being given therapy was 35.80 and the results showed The effect of restoring muscle and joint strength in post-op limb fracture patients in the working area of Muara Kumpeh Health Center with p-value (0,000) <α = 0.05. The conclusion of this study is the importance of ROOM therapy in post-op expression fracture patients. It is hoped that it can be used for patients to improve muscle strength systems and better recovery of mobilization activities